• 2022-06-30
    设[img=34x25]1803b2c775d1444.png[/img]在[img=35x25]1803b2c77de2c25.png[/img]二阶可微, [img=125x25]1803b2c7864b80a.png[/img] 且[img=138x28]1803b2c78f86e8c.png[/img] 则下列结论错误的个数为( )(1)方程[img=67x25]1803b2c797349af.png[/img]在[img=39x25]1803b2c79ecd96a.png[/img]内至少有一个实根;(2)方程[img=72x26]1803b2c7a615e76.png[/img]在[img=39x25]1803b2c79ecd96a.png[/img]内至少有两个实根;(3)方程[img=76x26]1803b2c7b62afdf.png[/img]在[img=39x25]1803b2c79ecd96a.png[/img]内至少有一个实根.
    A: [img=9x18]1803b2c7c657c06.png[/img]个
    B: [img=9x18]1803b2c7ce428b4.png[/img]个
    C: [img=9x18]1803b2c7d695198.png[/img]个
    D: [img=9x18]1803b2c7de39d54.png[/img]个
  • A

    举一反三

    内容

    • 0

      1.设随机变量X的密度为[img=186x61]18034ea953ec9dd.png[/img]则常数A=________,概率[img=146x25]18034ea95d30d08.png[/img]__________. A: A=2,P(X>1|X<2)=[img=39x24]18034ea9659b618.png[/img] B: A=-2,P(X>1|X<2)=[img=39x24]18034ea9659b618.png[/img] C: A=2,P(X>1|X<2)=[img=47x44]18034ea9768a8c2.png[/img] D: A=-2,P(X>1|X<2)=[img=47x44]18034ea9768a8c2.png[/img]

    • 1

      1.设随机变量X的密度为[img=186x61]17de8981070b17c.png[/img]则常数A=________,概率[img=146x25]17de8981130ab0e.png[/img]__________. 未知类型:{'options': ['A=2,P(X>;1|X<;2)=[img=39x24]17de89811f6f1b0.png[/img]', 'A=-2,P(X>;1|X<;2)=[img=39x24]17de89811f6f1b0.png[/img]', 'A=2,P(X>;1|X<;2)=[img=47x44]17de89812b3a28c.png[/img]', 'A=-2,P(X>;1|X<;2)=[img=47x44]17de89812b3a28c.png[/img]'], 'type': 102}

    • 2

      1.设随机变量X的密度为[img=186x61]17de8981070b17c.png[/img]则常数A=________,概率[img=146x25]17de8981130ab0e.png[/img]__________. 未知类型:{'options': ['A=2,P(X>;1|X<;2)=[img=39x24]17de89811f6f1b0.png[/img]', 'A=-2,P(X>;1|X<;2)=[img=39x24]17de89811f6f1b0.png[/img]', 'A=2,P(X>;1|X<;2)=[img=47x44]17de89812b3a28c.png[/img]', 'A=-2,P(X>;1|X<;2)=[img=47x44]17de89812b3a28c.png[/img]'], 'type': 102}

    • 3

      设集合[img=235x35]17e0bf8ae8a8338.png[/img],则A∪B=( ) 未知类型:{'options': ['{x|-1≤x<;2}', ' [img=110x35]17e0bf8af4dd8ac.png[/img]', ' {x|x<;2}', ' {x|1≤x<;2}'], 'type': 102}

    • 4

      求不定积分[img=121x54]17da653839aa6ae.png[/img]; ( ) A: log(x^2 + 3*x + 25/4)/4 + (5*atan(x/2 + 3/4))/4 B: log(x^2 + 3*x + 25/4)/4 C: (5*atan(x/2 + 3/4))/4 D: log(x^2 + 3*x + 25/4)/4 - (5*atan(x/2 + 3/4))/4